The relationship between coronary artery disease and depression and anxiety scores - Lutfu Askin; Kader Eliz Uzel; Okan Tanrıverdi; Veysi Kavalcı; Özkan Yavçin; Serdar Turkmen (İstanbul Kuzey Klinikleri, 2020)
Coronary artery disease (CAD) is one of the severe diseases that may cause significant moral and financial burden on society today. There are many studies in the literature on whether psychiatric disorders may cause CAD or an increase in prevalence after CAD. Although many studies have emphasized the importance of early diagnosis and treatment of depression in CAD patients, clinicians do not attach much attention to depression in daily practice. Several scales have been developed that are comfortable to use to describe anxiety and depression in CAD patients. High depression and anxiety scores predicted by psychological symptom scales following CAD treatment are closely related to treatment success and prognosis of the CAD. We believe that patients with CAD should be followed carefully for the diagnosis of depression and anxiety disorders; since the treatment of them may improve the prognosis of CAD.